Activation‐based association profiles differentiate network roles across cognitive loads. Issue 9 (10th March 2019) - Zuo, Nianming; Salami, Alireza; Yang, Yihong; Yang, Zhengyi; Sui, Jing; Jiang, Tianzi
Abstract: Working memory (WM) is a complex and pivotal cognitive system underlying the performance of many cognitive behaviors. Although individual differences in WM performance have previously been linked to the blood oxygenation level‐dependent (BOLD) response across several large‐scale brain networks, the unique and shared contributions of each large‐scale brain network to efficient WM processes across different cognitive loads remain elusive. Using a WM paradigm and functional magnetic resonance imaging (fMRI) from the Human Connectome Project, we proposed a framework to assess the association and shared‐association strength between imaging biomarkers and behavioral scales. Association strength is the capability of individual brain regions to modulate WM performance and shared‐association strength measures how different regions share the capability of modulating performance. Under higher cognitive load (2‐back), the frontoparietal executive control network (FPN), dorsal attention network (DAN), and salience network showed significant positive activation and positive associations, whereas the default mode network (DMN) showed the opposite pattern, namely, significant deactivation and negative associations. Comparing the different cognitive loads, the DMN and FPN showed predominant associations and globally shared‐associations. When investigating the differences in association from lower to higher cognitive loads, the DAN demonstrated enhanced association strength and globally shared‐associations, which were significantly greater than those of the other networks. This study characterized how brain regions individually and collaboratively support different cognitive loads.